Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Pada Sumatera Utara Tahun 2020-2022 - Syakiroh Afifah; Suci Ramadani; Vanessa Surya Wijaya; Jenny Zain; Oky Syahputra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Economic growth is influenced by several factors, including government spending. The size of government spending is highly dependent on revenue by the government itself (a certain time). One of the factors that influence economic growth in a government is Regional Original Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU) and Special Allocation Fund (DAK). Regional Economic Growth is often hampered due to low Regional Original Revenue which is unable to meet the needs of independent development. In addition, dependence on Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds often leads to budget inefficiencies, especially if allocations are uneven or late. This study aims to analyze the effect of PAD, DBH, DAU, and DAK on economic growth in North Sumatra Province using multiple linear regression analysis techniques. The results showed that individually PAD and DAU had a positive and significant influence on economic growth. On the other hand, DBH and DAK have a negative or insignificant effect on economic growth. This study concludes that PAD and DAU have a positive and significant effect on economic growth in North Sumatra Province, while DBH and DAK have no significant effect. Therefore, optimizing PAD and managing DAU more effectively need to be a priority to encourage economic growth. The greater the revenue received by the local government, the better because it positively affects economic development in the region.